2019
DOI: 10.1021/acs.biochem.9b00394
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3A Loop 1 Is a Determinant for Single-Stranded DNA Binding and Deamination

Abstract: The apolipoprotein B mRNA editing enzyme catalytic polypeptide-like 3 (APOBEC3 or A3) family of proteins functions in the innate immune system. The A3 proteins are interferon inducible and hypermutate deoxycytidine to deoxyuridine in foreign single-stranded DNA (ssDNA). However, this deaminase activity cannot discriminate between foreign and host ssDNA at the biochemical level, which presents a significant danger when A3 proteins gain access to the nucleus. Interestingly, this A3 capability can be harnessed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…A similar model was discussed by Solomon and coworkers, which demonstrated that loop 1 residues of hA3G-CTD-2K3A-E259A (a catalytically inactive form of A3G-CTD) strongly interact with substrate ssDNA and that this distinguishes catalytic binding from non-catalytic binding [81]. Interestingly, loop 1 of A3A was found to be important for substrate specificity but not for substrate binding affinity [82], while loop 1 of A3H especially residue R26, plays a triple role for RNA binding, DNA substrate recognition, and catalytic activity likely by positioning the DNA substrate in the active site for effective catalysis [83]. In accordance with this, our study claims that 25 RK 26 substitution in loop 1 of A3C provides the microenvironment that drives the flexibility in substrate binding and enzymatic activity.…”
Section: Discussionsupporting
confidence: 57%
“…A similar model was discussed by Solomon and coworkers, which demonstrated that loop 1 residues of hA3G-CTD-2K3A-E259A (a catalytically inactive form of A3G-CTD) strongly interact with substrate ssDNA and that this distinguishes catalytic binding from non-catalytic binding [81]. Interestingly, loop 1 of A3A was found to be important for substrate specificity but not for substrate binding affinity [82], while loop 1 of A3H especially residue R26, plays a triple role for RNA binding, DNA substrate recognition, and catalytic activity likely by positioning the DNA substrate in the active site for effective catalysis [83]. In accordance with this, our study claims that 25 RK 26 substitution in loop 1 of A3C provides the microenvironment that drives the flexibility in substrate binding and enzymatic activity.…”
Section: Discussionsupporting
confidence: 57%
“…A similar model was discussed by Solomon and coworkers, which demonstrated that loop 1 residues of hA3G-CTD-2K3A-E259A (a catalytically inactive form of A3G-CTD) strongly interact with substrate ssDNA and that this distinguishes catalytic binding from non-catalytic binding [81]. Interestingly, loop 1 of A3A was found to be important for substrate specificity but not for substrate binding affinity [82], while loop 1 of A3H especially residue R26, plays a triple role for RNA binding, DNA substrate recognition, and catalytic activity likely by positioning the DNA substrate in the active site for effective catalysis [83]. In accordance with this, our study claims that 25 Furthermore, the increased mobility of DNA binding regions carrying the substitutions in C2 and hA3C-S61P.S188I, respectively, compared to hA3C (Suppl.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies have suggested that loop 1 of A3A, which is shortest among all the AID/APOBEC enzymes, plays a key role in its high activity by making its active site more open ( 59 , 60 ). We wondered whether the presence of a larger loop 1 sequence in AID ( Supplementary Figure S5A ) could explain the enzyme's lack of preference for the more structured hairpin loop sequences.…”
Section: Resultsmentioning
confidence: 99%